Photocatalytic removal of 2-chlorophenol from water by using waste eggshell-derived calcium ferrite - Chaveanghong S. (2023)
A new approach to recycling low-value eggshell food waste was to produce a CaFe2O4 semiconductor with a narrow band gap (Eg = 2.81 eV) via hydrothermal treatments of powdered eggshell suspended in aqueous ferric salt (Fe3+) solutions at varying Fe loadings. It was possible to obtain a single phase of CaFe2O4 without any Ca(OH)2 and CaO impurities using an optimal Fe loading (30 wt% of Fe3+ by eggshell weight). The CaFe2O4 material was used as a photocatalyst for the breakdown of 2-chlorophenol (2-CP, a herbicide model chemical) as a pollutant in water. The CaFe2O4 with a Fe loading of 7.1 wt% exhibited a high 2-CP removal efficiency of 86.1% after 180 min of UV-visible light irradiation. Additionally, the eggshell-derived CaFe2O4 photocatalyst can be effectively reused, giving a high removal efficiency of 70.5% after the third cycle, without the requirement of regeneration processes (washing or re-calcination). Although radical trapping experiments confirmed that hydroxyl radicals were generated in the photocatalytic reactions, photogenerated holes play a significant role in the high 2-CP degradation efficiencies. The performance of the bioderived CaFe2O4 photocatalysts in the removal of pesticides from water demonstrated the benefits of resource recycling in the area of materials science and in environmental remediation and protection.